Country Village, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A rural village settlement.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Villages--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Coconut palm--Trinidad and Tobago